Rhodium-Catalyzed Direct Vinylene Annulation of 2-Aryloxazolines and Cascade Ring-Opening Using a Vinyl Selenone - Kitano, Junya; Nishii, Yuji; Hirano, Koji; Miura, Masahiro (Synlett, 2023)
Over the past two decades, transition-metal-catalyzed C–H activation and the subsequent oxidative cyclization with alkynes or their surrogates has emerged as a powerful synthetic tool for fused heteroaromatics. We report a Rh(III)-catalyzed annulation and ring-opening cascade reaction with 2-aryloxazolines. By utilizing a vinyl selenone as an oxidizing acetylene surrogate, the target three-component coupling products were obtained in high yields without using a stoichiometric amount of external oxidant.
Keywords: C–H bond activation; oxazolines; annulation; rhodium catalysis; vinylselenones; cascade reaction